11/9: a historical perspective. (1st January 2003) - Esquivié, Jean-Louis; Wybo, Jean-Luc
This paper presents some key elements about the origins of modern terrorism that help to understand the terrorist attacks against the twin towers in New York and the Pentagon in Washington, on September 11, 2001. Initially associated with the struggle against tyrants, terrorist action has been used to support different causes, which have in common the battle against current authority.